BAHASA SEBAGAI ALAT KOMUNIKASI PUBLIK DAN PEMBANGUNAN WACANA - Rahardjo, Mudjia (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2007)
Language is the most important tool we have for effective human communication, and the efficacy of communication is therefore directly related to the quality of this oral communication medium. The effectiveness of communication depends on several factors, the most important of which are the contents of the communication, the parties involved in the communication and the setting in which the communication takes place. Bad communication can lead to a complete breakdown in relationship and cause misunderstandings which quite often lead to conflicts between elements in the social structure. Effective communication has a very important role in creating an environment for reasoned debat, discussion and understanding in global society, and in this regard the current American approach to creating conducive to reasoned debate on the issue of global terrorisme is hypothesized to be in the less-than-effective category.